Optimizing nutrient removal and biomass production of the Algal Turf Scrubber (ATS) under variable cultivation conditions by using Response Surface Methodology - Gan, Xinyu; Klose, Holger; Reinecke, Diana (Frontiers in Bioengineering and Biotechnology, 2022)
This study investigated and optimized the nutrient remediation efficiency of a simple low-cost algal biofilm reactor, the algal turf scrubber (ATS), for wastewater treatment. Combined effects of three cultivation variables—total inorganic carbon, nitrogen-to-phosphorous (N:P) ratio, and light intensity—were examined. The ATS nutrient removal efficiency and biomass productivity were analyzed considering the response surface methodology (RSM). The maximum removal rates of total P and N were 8.3 and 19.1 mg L−1 d−1, respectively. As much as 99% of total P and 100% of total N were removed within 7 days. Over the same period, the dissolved oxygen concentration and pH value of the medium increased. The optimal growth conditions for simultaneous maximum P and N removal and biomass productivity were identified. Our RSM-based optimization results provide new insights into the combined effect of nutrient and light availability on the ATS remediation efficiency and biomass productivity.